2016
DOI: 10.1007/s10616-016-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence and expression profile of genes in buffalo (Bubalus bubalis) oocytes and embryos collected under different environmental stress

Abstract: The study examined the effects of different environmental stress on developmental competence and the relative abundance (RA) of various gene transcripts in oocytes and embryos of buffalo. Oocytes collected during cold period (CP) and hot period (HP) were matured, fertilized and cultured in vitro to blastocyst hatching stage. The mRNA expression patterns of genes implicated in developmental competence (OCT-4, IGF-2R and GDF-9), heat shock (HSP-70.1), oxidative stress (MnSOD), metabolism (GLUT-1), pro-apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…In support of these findings, another seasonal study reported lower expression of genes associated with oocyte maturation (fibroblast growth factor 16 [ FGF16 ] and GDF9 ) for both heifers and lactating cows during the summer (Ferreira et al, ). A similar pattern was reported for buffalo ( Bubalus bubalis ) oocytes; the relative abundance of OCT4 , insulin‐like growth factor 2 receptor ( IGF2R ) , GDF9, manganese‐dependent superoxide dismutase gene (MnSOD) and GLUT1 was lower in oocytes collected during the hot season relative to those collected during the cold season (Sadeesh, Sikka, Balhara, & Balhara, ). GDF9, IGF2R, and OCT4 (known as POU5F1) are mostly associated with developmental competence.…”
Section: Heat Stresssupporting
confidence: 68%
See 2 more Smart Citations
“…In support of these findings, another seasonal study reported lower expression of genes associated with oocyte maturation (fibroblast growth factor 16 [ FGF16 ] and GDF9 ) for both heifers and lactating cows during the summer (Ferreira et al, ). A similar pattern was reported for buffalo ( Bubalus bubalis ) oocytes; the relative abundance of OCT4 , insulin‐like growth factor 2 receptor ( IGF2R ) , GDF9, manganese‐dependent superoxide dismutase gene (MnSOD) and GLUT1 was lower in oocytes collected during the hot season relative to those collected during the cold season (Sadeesh, Sikka, Balhara, & Balhara, ). GDF9, IGF2R, and OCT4 (known as POU5F1) are mostly associated with developmental competence.…”
Section: Heat Stresssupporting
confidence: 68%
“…GLUT1 is a regulatory molecules of glucose uptake (i.e., glucose transporter) which plays a pivotal role in embryonic metabolism (Niemann & Wrenzycki, ). Similar to GAPDH, the reduced GLUT1 expression suggested a seasonal effect on metabolism‐associated genes, which in turn reduced embryonic development in the hot season (Sadeesh et al, ), presumably due to compromised metabolism. MnSOD encodes an antioxidant enzyme (SOD2) related to the cellular response to oxidative stress that may protect cells from oxidative damage (Christianson, ).…”
Section: Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore many studies have been carried out on bovine oocytes related to heat stress to find the cause behind these catastrophic effects on oocyte competency (Payton et al ., 2004; Ju et al ., 2005; Roth & Hansen, 2005; Paula-Lopes et al ., 2008; Nabenishi et al ., 2012; Maya-Soriano et al ., 2013, Pavani et al ., 2016). To date, the availability of published data on the effect of heat stress on bubaline oocytes and embryos has been very limited (Khairy et al ., 2007; Yadav et al ., 2013, Abdoon et al ., 2014; Ashraf et al ., 2014, 2016; Sadeesh et al ., 2016) and there is no literature available investigating the mechanisms by which heat shock can cause such catastrophic effects on buffalo COCs. Therefore, it appears necessary to define the molecular mechanisms that identify potential local effects of elevated heat temperature on buffalo cumulus–oocyte complexes (COCs) and oocyte developmental competence.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes recovered during the summer have exhibited lower quality (Rutledge et al ., 1999; Al-Katanani et al ., 2002), and reduced developmental potential (Rutledge et al ., 1999; Al-Katanani et al ., 2002; Paula-Lopes et al ., 2008) and pre-implantation embryonic development (Paula-Lopes & Hansen, 2002). In buffaloes, elevated temperatures in the summer reduced the yield of good quality oocytes, maturation and cleavage rates and yield of embryos that developed to the blastocyst stage (Sadeesh et al ., 2016). In addition, Abdoon et al .…”
Section: Introductionmentioning
confidence: 99%